POETICS HISTORICAL DEVELOPMENT IN THE CONTEXT OF KULT TEXTS - Fethi DEMİR (Fırat University, 2019)
Poetics, which identies with analysing of poems in our today, studies subjects including its form, content, style and aesthetic without depending on a certain example is a science emerging by the birth of literature, developing, and turning into the studty of literary genres in time. During the history, Poetics conceptualized as a term by Aristoteles, and an example of avant-garde has gained various meanings and